USING PROBLEM-BASED LEARNING IN THE STUDY OF V. RASPUTIN’S WORKS (International Conference on Education, Psychology and Humanities, 2026)
This article examines the pedagogical possibilities of problem-based learning in the study of Valentin Rasputin’s prose, with particular attention to the formation of interpretive competence, moral reflection, dialogic thinking and value-oriented reading among learners. Rasputin’s artistic world is especially productive for problem-based literary education because his narratives do not merely describe events; they place the reader before ethically tense situations in which memory, conscience, responsibility, family, childhood, village culture, historical rupture and human dignity become objects of intellectual and moral inquiry.
Keywords: Problem-based learning, Valentin Rasputin, literary education, interpretive competence, moral reflection, Russian literature, pedagogical technology, critical thinking, dialogic method, value-based education.